The Distribution of Wealth and Welfare in the Presence of Incomplete Annuity Markets - Eckstein, Zvi; Eichenbaum, Martin S.; Peled, Dan (Quarterly Journal of Economics, 1985)
This paper examines the implications of the absence of complete annuity markets on the distribution of wealth and welfare of agents whose saving decisions are obtained under uncertainty regarding the length of their life. The absence of annuities is shown to yield a unique nondegenerate intragenerational distribution of wealth, which is fully characterized. This characterization is then used to evaluate the Pareto desirability of an annuity system. Alternative welfare criteria that can be used when the proposed change has differential impacts on the initial state of subsequent generations are considered.